Characteristics of smaller company leveraged buyouts - Malone, Stewart C. (Journal of Business Venturing, 1989)
While stories abound in the business press about multibillion dollar leveraged buyouts (LBOs), scant attention has been paid to this type of buyout financing in smaller companies. Some observers argue that LBOs are little more than financial manipulation, while others suggest that they are an alternative form of entrepreneurial endeavor and that smaller company LBOs may serve to rejuvenate formerly stodgy organizations. In this study, data from 56 firms that experienced an LBO between 1981 and 1987 were analyzed to ascertain the current state of smaller company LBOs and what changes, if any, occur after the LBO takes place. Most of the smaller company LBOs occur in industries far different from the high-growth, high-technology environments of the glamorous start-up. The cash flow requirements of the high debt component seem to favor industries in which growth is very slow or even negative and in which the technology is stable. Likewise, smaller LBOs are relatively immune from foreign competition. The typical smaller company LBO individual has generally been associated with the company as an officer or director prior to the buyout, and possesses at least a college education. While it was presumed that the typical LBO individual would be between 40 and 55 years of age, a substantial number of both older and younger individuals were discovered in the study. In terms of internal operating changes after the buyout, it was expected that the locus of decision making would shift toward the lead investor and that managerial compensation would become increasingly incentive based. Unexpectedly, little change in the locus of decision making occurred, but there was a pronounced shift away from salaried compensation. Sample firms indicated that asset stripping or personnel layoffs occurred relatively infrequently, and the most common operating changes focused on such revenue-generation efforts as increased sales and marketing and on imposing more stringent capital budgeting requirements. The study suggests that the once-stable environments in which these firms operated may become far more exciting in the future. On the positive side, these smaller companies are being operated by owner-managers experienced in both the company and the industry. The financial requirements of the high debt levels and the resulting emphasis on cash flow rather than profitability may make these firms extremely fierce competitors. On the negative side is the instability that may be caused by the high debt levels. Because most of these companies have not yet faced an economic recession, their long-term viability remains to be tested.